Assist-Pro: Um Assistente Baseado em Conhecimento para Apoiar a Definição de Processos de Software - Falbo, Ricardo de Almeida; Menezes, Crediné Silva de; Rocha, Ana Regina C. da (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 1999: Anais do XIII Simpósio Brasileiro de Engenharia de SoftwareDO - 10.5753/sbes.1999.23919, 1999)
An important requirement for software quality is to define a software development process. However, software process definition is a complex activity that requires intensive use of knowledge. So, it is worth to offer knowledge-based support to this activity. In this paper we present Assist-Pro, a knowledge-based assistant to aid software engineers to define software processes. We also discuss its development process using knowledge components available in a Knowledge Server.